Bamboo shoot dietary fiber alleviates gut microbiota dysbiosis and modulates liver fatty acid metabolism in mice with high-fat diet-induced obesity - Zhou, Xiaolu; Ma, Lingjun; Dong, Li; Li, Daotong; Chen, Fang; Hu, Xiaosong (Frontiers in Nutrition, 2023)
Obesity is a common nutritional disorder characterized by an excessive fat accumulation. In view of the critical role of gut microbiota in the development of obesity and metabolic diseases, novel dietary therapies have been developed to manage obesity by targeting the gut microbiome. In this study, we investigated anti-obesity effects of bamboo shoot dietary fiber (BSDF) and the potential mechanisms. We intervened with BSDF in mice fed a high-fat dietfor 12 weeks and found that BSDF was effective in reducing lipid accumulation in liver and adipose tissue and alleviating dyslipidemia and insulin resistance. Liver transcriptome analysis results showed that BSDF could improve lipid metabolism and liver injury by modulating peroxisome proliferator-activated receptor (PPAR) and fatty acid metabolic pathways. The 16S rRNA gene sequencing analysis of gut microbiota composition showed that BSDF significantly enriched beneficial bacteria such as Bifidobacterium, Akkermansia, Dubosiella, and Alloprevotella. Analysis of fecal metabolomics and gut microbiota metabolites revealed that BSDF increased the levels of several short-chain fatty acidsand enriched bile acids, which may be important for improving lipid metabolism. Notably, the obesity-related metabolic disorders were abrogated after the abrogation of gut microbiota, suggesting that gut microbiota is a key factor in the beneficial effects of BSDF. Our study suggests that BSDF as a prebiotic supplement has the potential to improve obesity by improving gut microbiota and modulating host PPAR and fatty acid metabolic pathways.